Elite sport - return to competition: safe return of spectators (2020)
The following guidance provides a set of minimum standards to progress from Stage Four: Return to Cross Border Competition - No Spectators (RTCBC) to Stage Five: Return to Competition - Safe Return of Spectators (RTCSRS). The guidance allows for spectators to return to competition in a controlled and socially distanced (SD) way at reduced capacity in competition venues.